Malignant Schwannoma of the Esophagus: A Rare Case Report - Mishra, Biswajit (Korean J Thorac Cardiovasc Surg, 2016)
Neurogenic tumors are the most prevalent tumors of the mediastinum, and schwannomas are the most common type of neurogenic tumor. Primary neurogenic neoplasm of the esophagus is uncommon and malignant schwannoma of the esophagus is extremely rare. We report a case of a 27-year-old female presenting with dysphagia and palpitations who was found to have a lobulated tumor in the mediastinum that was compressing the esophageal lumen. The tumor was successfully treated surgically without recurrence. The final diagnosis, on histopathological examination of the specimen, was malignant schwannoma.